Degenerative-Dystrophic Changes in the Cervical Spine at an Early Age - o‘g‘li, Ashirov Farruxbek Azamat; qizi, Ashirova Noila Abror; Ilkhomovna, Kamalova Malika (Journal of Science in Medicine and Life, 2024)
Neck pain usually occurs in response to awkward movement, trauma or inflammation of any of the structures of the cervical spine. In addition, the cause of pain can be overstretching of muscles or ligaments, for example, when lifting weights, unsuccessful turning of the head or against the background of arthrosis of the very joints between the articular processes. ‘Pinched nerve’, or cervical radiculopathy, specific processes (metastases, tumours of vertebrae, spinal cord sheaths in the cervical region) are relatively rare.